2022
DOI: 10.1155/2022/3864758
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Silver Nanoparticles Fabricated by Euphorbia granulata Forssk’s Extract: Investigating the Antimicrobial, Radical Scavenging, and Catalytic Activities

Abstract: The plants of Euphorbiaceae have high medicinal values and their phytochemical composition plays a major role in metal ion reduction. In this research, Euphorbia granulata (EG) the “spurge family” plant extract was used to reduce silver ions to silver nanoparticles (AgNPs). This nanoparticle formation was observed by UV-VIS spectrophotometric analysis at different times and temperatures to achieve the most optimal conditions. The synthesized biogenic silver nanoparticles (EG-AgNPs) were subjected to FTIR studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Several research investigations, such as Periasamy et al [65], Periyasami et al [66], Phuyal et al [41], and Khanal et al [38], have shown the occurrence of silver nanoparticles with strong biological activity.…”
Section: Resultsmentioning
confidence: 99%
“…Several research investigations, such as Periasamy et al [65], Periyasami et al [66], Phuyal et al [41], and Khanal et al [38], have shown the occurrence of silver nanoparticles with strong biological activity.…”
Section: Resultsmentioning
confidence: 99%
“…This graph shows the relationship between time and dye concentration at various periods after 3 h of exposure to visible light. Periyasami et al (2022) recently investigated that the Euphorbia granulata synthesized Ag-NPs showed promising catalytic properties against methylene blue and methylene orange organic dyes. Likewise, Kumar et al (2013) have investigated the degradation of methyl orange dye using Ag-NPs produced from Ulva lactua.…”
Section: Discussionmentioning
confidence: 99%
“…Several research investigations, such as Periasamy et al [67], Periyasami et al [68], Phuyal et al [44], and Khanal et al [41], have shown the occurrence of silver nanoparticles with strong biological activity. The process of phytochemical screening involves both qualitative and quantitative analysis of chemical classes present in ethnomedicinal plant species.…”
Section: Plos Onementioning
confidence: 99%